Prognostic impact of tumor lymphocytic infiltrates in patients with breast cancer undergoing neoadjuvant chemotherapy - Avci, Nilufer; Deligonul, Adem; Tolunay, Sahsine; Cubukcu, Erdem; Olmez, Omer Fatih; Altmisdortoglu, Ozgur; Evrensel, Turkkan (Imprimatur Publications, 2015)
Purpose: The presence of a pronounced tumor lymphocytic infiltrate (TLI) is deemed to reflect the presence of an immunoinflammatory response against the tumor and may thus have prognostic significance. We investigated the prognostic value of TLI detected in pathological specimens collected following neoadjuvant chemotherapy (NACT) in patients with breast cancer. Methods: 100 consecutive patients with breast cancer (mean age 47.8 +/- 11.4 years) who were scheduled to undergo anthracycline- and/or taxane-containing NACT were enrolled. Specimens collected after NACT were scored with the 4-point Klintrup scoring criteria for the presence of TLI. Results: 60 patients had low-grade TLI and 40 high-grade TLI. Comparison of the patient population according to low-grade vs high-grade TLI revealed statistically significant difference both in terms of disease-free survival (DFS) (log rank=4.28, p<0.05) and overall survival (OS) (log rank=3.96, p<0.05), with high-grade TLI patients showing a better prognosis. Multivariate Cox regression analysis identified postoperative tumor size and low-grade TLI as the two main independent adverse prognostic factors. Conclusion: High-grade TLI may interfer with tumor growth and can represent a favorable prognostic factor in women with breast cancer undergoing NACT.
Keywords: breast cancer; neoadjuvant chemotherapy; prognosis; tumor lymphocytic infiltrates